Evaluasi Penggunaan Obat Antihipertensi Pada Pasien Penyakit Ginjal Kronik Di Ruang Rawat Inap Rumah Sakit X Tangerang - Muthia Nurhidayah; Nuraini Nuraini; Sefi Megawati (Jurnal Pharmacopoeia, 2026)
Chronic kidney disease (CKD) has become an increasingly important public health problem in Indonesia, in parallel with the rising prevalence of hypertension. Data from the 2018 Basic Health Research (Riskesdas) indicated that the prevalence of chronic kidney failure in Indonesia remained a serious concern, and at RSU Kab. Tangerang, CKD was among the diseases with a high incidence, with hypertension as the main comorbidity. This study aimed to evaluate patterns of antihypertensive drug use in hospitalized CKD patients, including the appropriateness of patient selection, indications, drug selection, and dosing. A descriptive study design was applied using retrospective data obtained from the medical records of CKD patients treated in the inpatient ward of RSU Kab. Tangerang during the most recent study period. The data collected included patient characteristics, types of antihypertensive drugs prescribed, serum creatinine levels, blood pressure measurements, and patients’ clinical conditions. The results showed that 41.6% of patients received monotherapy, while 58.3% received combination therapy. The most commonly prescribed antihypertensive drugs were captopril, ramipril, valsartan, telmisartan, furosemide, bisoprolol, amlodipine, nifedipine, and clonidine. Evaluation of antihypertensive drug use revealed 100% appropriateness in indications, 98.33% appropriateness in drug selection, and 96.66% appropriateness in dosing. In conclusion, the use of antihypertensive drugs in hospitalized CKD patients RSU Kab. Tangerang was largely rational and consistent with therapeutic guidelines; however, continuous evaluation is still required to further improve the quality of therapy.